The Politics of Assimilation of the Tea-Garden Community of Assam with The Greater Assamese Society: - et al., Dr Phulmoni Das (International Journal of Advanced Science and Technology, 2019)
Tea garden community of Assam has been playing an important role in shaping the political milieu of Assam. Tea garden workers of Assam has a history of millions of colonial migrant workers, who has worked under the condition of indentured servitude in tea plantation in Assam, producing tea for an increasingly profitable global market. Ever since the colonial period the socio economic condition of tea garden workers has hardly improved even today. Based on these inferior conditions of tea plantation workers, they are called the ‘Subalterns’. In spite of their contributions to the growth of tea plantation in Assam, their socioeconomic condition depicts the legacy of exploitation since pre independence. Migrant labours that were brought to Assam from different parts of India and were settled across the plantation areas constituted the very core of the tea plantation in Assam. In Assam they are known by different nomenclatures such as Cooley, Bongali, Bagania, Chah Shramik etc in colonial period, again as Tea community, Tea tribes, Adivasis, Ex- tea garden labour community etc in present times. But the fact remained that each member of the tea and ex-tea garden community primarily is a member of an ethnic, religious and socio cultural group. As these tea garden workers originated from different ethnic background, they had to make a tough struggle for adjustment in a completely new environment and in the process of adjusting with the situation some major transformation were observed in their life. Therefore in this context the present paper is an attempt to understand the politics of assimilation of tea garden community of Assam with that of the larger Assamese community and the paper also highlights that during the course of the assimilation process there is the revival of the Adivasi identity which has been observed among the tea garden community of Assam.